1998
DOI: 10.3168/jds.s0022-0302(98)75842-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Cholesterol in Milk and Milk Products by Direct Saponification and Capillary Gas Chromatography

Abstract: A simple method is described for the determination of cholesterol in milk and milk products. Samples (0.2 g) are saponified in capped tubes with 0.5 M methanolic KOH solution by heating for 15 min at 80 degrees C. Water is added to the mixtures, and the unsaponifiable fractions are extracted with hexane to be further analyzed by capillary gas chromatography. Because of the rapid sample preparation and gas chromatographic procedures, a single sample can be analyzed in 30 min. Overall recovery was 98.6%, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 15 publications
4
84
0
1
Order By: Relevance
“…Fletouris et al [13] obtained the following values in ovine, bovine and caprine milks: 21.7 ± 0.32, 12.2 ± 0.18 and 14.4 ± 0.22 mg·100 g -1 of milk; the content in ewe's milk is similar to that found in this study. Table I also shows the concentrations of the minor sterols.…”
Section: Quantificationsupporting
confidence: 76%
See 1 more Smart Citation
“…Fletouris et al [13] obtained the following values in ovine, bovine and caprine milks: 21.7 ± 0.32, 12.2 ± 0.18 and 14.4 ± 0.22 mg·100 g -1 of milk; the content in ewe's milk is similar to that found in this study. Table I also shows the concentrations of the minor sterols.…”
Section: Quantificationsupporting
confidence: 76%
“…Human milk contains desmosterol [12], lathosterol, dihydrolanosterol, lanosterol, a dimethylsterol (4a,b-dimethyl-5a-cholest-8,24-dien-3b-ol), methostenol (4a-methyl-5a-cholest-8,24-dien-3b-ol) and squalene [21]. There is not enough information about the content of cholesterol and other sterols in ewe's milk; however, some authors have reported a slightly higher level of cholesterol as compared with cow's milk [13].…”
Section: Introductionmentioning
confidence: 93%
“…The values of milk cholesterol concentration in the present study are comparable to those observed by Fletouris et al (1998) with goat milk obtained from a local milk industry in Greece (14.4 mg/100 g). In our study, HSO supplementation had no influence on milk cholesterol concentration, but it numerically increased plasma cholesterol concentration.…”
Section: Plasma Lipid Profile and Enzymatic Activitiessupporting
confidence: 76%
“…Cholesterol was determined by the procedure described by FLETOURIS et al (1998). For the preparation of cholesterol standards, the stock solution (2 mg/ml) was prepared by dissolving 20 mg of the reference standard (Sigma Chemical Company, St. Louis, MO, USA) in hexane in a 10 ml volumetric flask.…”
mentioning
confidence: 99%